2016
DOI: 10.1038/srep21772
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces autophagy by directly inhibiting mTOR through ATP competition

Abstract: Resveratrol (RSV) is a natural polyphenol that has a beneficial effect on health, and resveratrol-induced autophagy has been suggested to be a key process in mediating many beneficial effects of resveratrol, such as reduction of inflammation and induction of cancer cell death. Although various resveratrol targets have been suggested, the molecule that mediates resveratrol-induced autophagy remains unknown. Here, we demonstrate that resveratrol induces autophagy by directly inhibiting the mTOR-ULK1 pathway. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(178 citation statements)
references
References 47 publications
7
164
1
2
Order By: Relevance
“…We then investigated the molecular mechanism underlying this apoptotic pathway. Previous reports have suggested that resveratrol has the capability to induce autophagy and might also play a role in enhancing apoptosis [54][55][56]. However, our western blot results revealed that treatment with different concentrations of resveratrol increased LC3-II accumulation and decreased p62 expression levels in A549 cells, thus confirming the activation of complete autophagy flux by lysosomal degradation (Fig.…”
Section: Discussioncontrasting
confidence: 50%
“…We then investigated the molecular mechanism underlying this apoptotic pathway. Previous reports have suggested that resveratrol has the capability to induce autophagy and might also play a role in enhancing apoptosis [54][55][56]. However, our western blot results revealed that treatment with different concentrations of resveratrol increased LC3-II accumulation and decreased p62 expression levels in A549 cells, thus confirming the activation of complete autophagy flux by lysosomal degradation (Fig.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been determined that resveratrol dose-dependently reduced the vascular endothelial growth factor (VEGF), leptin, interleukin (IL)-6, and IL-8 expression in hypoxia-induced human adipocytes and prevented adipokine-induced inflammation and angiogenesis [51]. In addition, resveratrol induced autophagy by directly inhibiting mTOR in HeLa cells [52]. Prostate cancer cells induced autophagy through inhibition of the Akt/mTOR pathway in PC3 and DU145 cells [53].…”
Section: Gene Expression and Regulation In Mammalian Cells -Transcripmentioning
confidence: 99%
“…In this manner, energy and building blocks can be generated from the cell’s own protein and lipid stores. Nutrient-stimulated activation of mTOR leads to the phosphorylation and inactivation of components of the autophagy pathway [149], specifically ULK1 [148]. This process, shown in the GP [144, 145], is associated with nutrition-induced regulation of growth attenuation.…”
Section: Local Molecular Mechanisms In Malnutrition and Cu Growthmentioning
confidence: 99%
“…When AMP kinase or HIF1α activity were blocked, autophagy could not be activated [147]. mTORC1 suppresses catabolism by inhibiting autophagy through suppression of the autophagy complex ULK1-ATG13-FIP200, specifically through inhibitory phosphorylation of ULK1 [148]. Inhibition of mTORC1 is sufficient to induce autophagy.…”
Section: Local Molecular Mechanisms In Malnutrition and Cu Growthmentioning
confidence: 99%